2018
DOI: 10.17743/jaes.2018.0007
|View full text |Cite
|
Sign up to set email alerts
|

Co-design of a Smart Cajón

Abstract: Smart Instruments are a novel family of musical instruments that embed sensors, actuators, wireless connectivity, and semantic audio technologies. This paper reports the findings of a participatory design approach to develop a Smart Cajón, a box-shaped percussion instrument with Internet of Musical Things components. Five initial co-design sessions were conducted with different professional cajón player participants. The players were invited to devise tangible mock-ups by placing provided sensors on an acousti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Therefore, the rendering of the simulated percussive instrument sounds cannot be informed by a plethora of data describing how and where the hit was performed. Consequently, as stated by some of the cajón players we worked with in a previous study (Turchet et al, 2018), the quality of the gesture-to-electronic sound interaction is largely impoverished compared to the level of control intimacy of the acoustic cajón. Enabling subtle interaction and nuances in electronically-controlled cajones is deemed crucial by players (Turchet et al, 2018) and is the focus of the current study.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Therefore, the rendering of the simulated percussive instrument sounds cannot be informed by a plethora of data describing how and where the hit was performed. Consequently, as stated by some of the cajón players we worked with in a previous study (Turchet et al, 2018), the quality of the gesture-to-electronic sound interaction is largely impoverished compared to the level of control intimacy of the acoustic cajón. Enabling subtle interaction and nuances in electronically-controlled cajones is deemed crucial by players (Turchet et al, 2018) and is the focus of the current study.…”
Section: Introductionmentioning
confidence: 93%
“…The design process was informed not only by the results of the study reported in Turchet et al (2018), but also by consultations with three professional cajón players who were involved in codesign and testing sessions before the final evaluation.…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Another instance of SMIs is the smart cajón reported in [55]. This instrument consists of a conventional acoustic cajón smartified with sensors, Wi-Fi connectivity, motors for vibrotactile feedback, the Bela board for low-latency audio and sensors processing [56], which runs a sound engine composed by a sampler and various audio effects.…”
Section: Musical Thingsmentioning
confidence: 99%